2010
DOI: 10.1074/jbc.m110.170209
|View full text |Cite
|
Sign up to set email alerts
|

Sequences from the First Fibronectin Type III Repeat of the Neural Cell Adhesion Molecule Allow O-Glycan Polysialylation of an Adhesion Molecule Chimera

Abstract: Polysialic acid is a developmentally regulated, anti-adhesive polymer that is added to N-glycans on the fifth immunoglobulin domain (Ig5) of the neural cell adhesion molecule (NCAM). We found that the first fibronectin type III repeat (FN1) of NCAM is required for the polysialylation of N-glycans on the adjacent Ig5 domain, and we proposed that the polysialyltransferases recognize specific sequences in FN1 to position themselves for Ig5 N-glycan polysialylation. Other studies identified a novel FN1 acidic surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
20
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 51 publications
1
20
0
Order By: Relevance
“…We found that when either the FN1 ␣-helix or QVQ sequence of NCAM was replaced with alanines, the polySTs continued to recognize the mutant proteins but added polysialic acid to O-glycans on FN1 rather than N-glycans on Ig5 (39,42), suggesting that these sequences play a role in positioning the polySTs for N-glycan polysialylation. The importance of the FN1 acidic patch varies in N-glycan and O-glycan polysialylation.…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…We found that when either the FN1 ␣-helix or QVQ sequence of NCAM was replaced with alanines, the polySTs continued to recognize the mutant proteins but added polysialic acid to O-glycans on FN1 rather than N-glycans on Ig5 (39,42), suggesting that these sequences play a role in positioning the polySTs for N-glycan polysialylation. The importance of the FN1 acidic patch varies in N-glycan and O-glycan polysialylation.…”
mentioning
confidence: 98%
“…Molecular modeling and structural analysis of NCAM FN1 showed two novel features not seen in other fibronectin type III repeats, a surface acidic patch composed of Asp 506 , Asp 520 , Glu 521 , and Glu 523 and an ␣-helix linking strands 4 and 5 of the FN1 ␤ sandwich (39,40). Two other unique FN1 sequences, 510 PYS 512 and 516 QVQ 518 (QVQ), were also identified (42). The role of all four sequences in NCAM polysialylation was analyzed by mutagenesis and the creation of chimeric proteins.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although the FN1 domain of OCAM could partially replace that of NCAM to support polyST recognition and polysialylation, and N-glycans were present in appropriate locations on the OCAM Ig5 domain, other sequences in the OCAM Ig5 domain served to block a stable interaction and OCAM polysialylation (28,29). In addition, the FN1 domain of OCAM had a weak polyST recognition site with only one of the three acidic patch residues found in the NCAM FN1 present; inserting the other two acidic residues substantially increased OCAM polysialylation when the blocking sequences in the OCAM Ig5 domain were removed (28).…”
Section: Discussionmentioning
confidence: 99%
“…At 80 -90% confluence, cells were transfected using 3 g of V5-or Fc-tagged NRP cDNA and ST8SiaIV-Myc cDNA (cloning of ST8SiaIV cDNA into the pcDNA3.1 Myc/HisB expression was described previously (29)) and 30 l of Lipofectin in 3 ml of Opti-MEM I and incubated at 37°C in a 5% CO 2 incubator, according to the manufacturer's protocol. After a 6-h incubation, 7 ml of DMEM, 10% FBS, 1% pencillin/streptomycin was added to each plate and incubated for an additional 18 -24 h.…”
Section: Analysis Of Nrp-1 Nrp-2 and Chimeric Protein Localization mentioning
confidence: 99%